Formation of Coalitions in Self-Enforcing International Environmental Agreements - Peter Yu, Peixin (International Journal of Global Economics and Management, 2024)
Climate change is not a solved issue in the world today: countries are not willing to mitigate for the benefit of everyone. It thus becomes necessary to investigate the reason for the lack of cooperation for a potential solution. This essay plans on modeling the payoffs of players in the international mitigation game, reaching the results that without an incentive provided by the coalition, players are unlikely to mitigate. Moreover, unequal relationships between countries can result in certain countries mitigating themselves while not encouraging their subordinate countries to mitigate.